Education in Turkey in terms of gender asymmetry - Düzgün Fatih; Metresh Eda Havva Tan; Pozdnyakova Alina Aleksandrovna; Grafkova Tatiana Stanislavovna; Kalita Marina Evgenievna (SHS Web of Conferences, 2021)
The wide representation of women at different levels of the education system is not only an indicator of the prestige and status of the teaching profession, but also an important indicator of the socio-cultural and political development of society. The purpose of this article is to analyze the Turkish education system in terms of gender asymmetry. The research problems include: 1) the study of the historical reasons that led to the phenomena of gender asymmetry in certain “zones” and at certain levels of education; 2) the study of the motives for choosing a teaching profession by women of different age groups; 3) determination of the social profile of a Turkish female teacher; 4) the formation of recommendations for overcoming gender asymmetry in the field of Turkish education. Contrary to prejudice, Turkey is not a “gender bounded” country; moreover, its educational system is subject to problems common to the systems of most developed countries. The main ones are: 1) underrepresentation of female teachers in higher education (with a tendency to reduce the gender gap) and 2) underrepresentation of women in leadership positions. Despite the fact that all conditions have been created in Turkey for the professional development of a female teacher, the mentality of the average Turkish woman does not allow her to put her career interests above the interests of her family. This, in our opinion, largely explains the “restriction” of female education at the level of secondary specialized and insufficient “popularity” of higher education. For further study of the manifestations of gender asymmetry, a more detailed study of all stages of the Turkish education system is required, using data from different regions, in particular, from the southeast region. The situation there may differ significantly from the situation in the central regions, and the problem of adapting the education system to regional conditions will be extremely relevant.